An integrative approach to construction development: from efqm-based conceptual modeling to the formation of a digital ecosystem - Konchakivskyi, Oleksii; Bartko, Vasyl; Khomenko, Oleksandr; Petrenko, Alexandr (Ways to Improve Construction Efficiency, 2024)
The article explores theoretical and practical aspects of forming a conceptual management model in the field of construction development under conditions of dynamic market changes, accelerating digital transformation, and increasing demands for management quality. The relevance of the topic is driven by the need to create integrated models that enable developers to make strategically grounded decisions, taking into account multi-level stakeholder interaction, risks, and technological changes. The problem statement highlights the insufficient adaptability of traditional technocratic approaches to the modern realities of implementing complex infrastructure and residential-commercial projects, which require interdisciplinary integration of engineering accuracy, economic efficiency, and social feasibility. To address this, the author proposes adapting approaches from engineering psychology and ergonomics—particularly conceptual modeling of operator behavior in complex information-technical systems—to the practice of managing developer structures. The article presents a systematization of analytical indicators for evaluating key components of a development conceptual model, including architectural and planning decisions, financial and investment parameters, regulatory compliance, stakeholder behavior, spatial development scenarios, and digital management tools. Moreover, it examines the applicability of the international EFQM (European Foundation for Quality Management) model and its operational RADAR framework in shaping assessment logic for management practices in construction. As a result, the author substantiates the relevance of developing a multifactorial conceptual model as a cognitive-managerial foundation for the strategic development of developer enterprises. It is concluded that the implementation of such models enhances decision-making accuracy, digital maturity, and the formation of resilient approaches to project management in the construction sector.